Gas and Electricity Market Design for a Flexible Operation of Gas-fired Power Plants - Karsten Neuhoff; Sophia Ruester; Sebastian Schwenen (Deutsches Institut für Wirtschaftsforschung, 2014)
Gas-fired power plants constitute a direct and important link between the gas and the electricity sectors and thus between the Target Models for electricity and gas. As the need for a flexible operation of gas-fired power plants will increase in tomorrow's low-carbon power markets, so also will the challenges for market design of both sectors in allowing for flexible trading arrangements. For the electricity markets, options to advance intraday and balancing market design are currently discussed, such as complex bids, the frequency of intraday and balancing market clearing, and the joint optimization of energy and reserve markets. For the gas market, concrete options for design advances are yet to be explored. The success – and the flaws – of the implementation of the new EC Network Codes for gas will provide new food for debates. Last, the interaction between gas and electricity TSOs in balancing the heavily interlinked short-term electricity and gas markets poses a need for (more) coordination between the different types of TSOs.
Keywords: Q41; Q42; Q48; L94; L95; 330; Gas and Electricity Market Design; Gas-fired Power Plants; Gas and Electricity Market Design; Gas-fired Power Plants